Status of serum and salivary ascorbic acid in oral potentially malignant disorders and oral cancer - Supriya Bhat; Subhas Gogineni Babu; Saidath K Bhat; Renita Lorina Castelino; Kumuda Rao; Medhini Madi (Indian Journal of Medical and Paediatric Oncology)
Background and Aims: The aim of this study was to estimate the detoxification status of serum and saliva by assessing the serum and salivary Vitamin C in oral potentially malignant disorders and oral cancer. Subjects and Methods: A total of 90 subjects, 30 subjects with oral potentially malignant disorders, 30 subjects with oral cancer, and 30 healthy subjects (controls) were included in the study. Serum and saliva were collected and levels of Vitamin C were assessed. Data obtained was analyzed using ANOVA test for the comparison between the groups. Post hoc Tukey's analysis was used for the comparison of the two study groups to the control group. Correlation between the groups was done using Pearson's correlation coefficient test. Results: The mean serum and salivary Vitamin C levels were decreased significantly in potentially malignant disorders and oral cancer when compared to healthy subjects. Conclusions: As significant reduction of Vitamin C is seen in saliva, it can be stated that saliva can be used as a reliable, noninvasive biomarker in diagnosis and management of potentially malignant disorders and oral cancer.